Partial Recovery of Macro-Epibenthic Assemblages on the North-West Shelf of the Black Sea - Stevens, Tim; Mee, Laurence; Friedrich, Jana; Aleynik, Dmitry; Minicheva, Galina (Frontiers in Marine Science, 2019)
The north-west shelf of the Black Sea has suffered well-documented declines in biodiversity since the 1960s, and by the 1990s was considered a dead zone with virtually no sign of macroscopic epibenthic life. It was characterised by high levels of anthropogenic input, massive phytoplankton blooms, and periodically hypoxic to anoxic bottom waters. An important contributor to primary production on the northwest shelf is the red alga Phyllophora spp. growing in waters to 70 m depth. Phyllophora is a habitat forming taxon supporting complex assemblages of bivalves, sponges, and ascidians, with an associated rich fish fauna. From 1990 on, nutrient loads entering the system plummeted and the severity of algal blooms decreased. Changes to benthic communities, however, were far less rapid, and the trajectory and rate of any recovery of the dead zone, in particular Zernov’s Phyllophora Field, is far from certain. This study used towed underwater video imagery from research cruises in summer 2006 and spring 2008 to classify and map macro-epibenthic assemblage structure, and related this to putative physical, chemical and spatial drivers. Distinct and relatively stable benthic communities were in evidence across the northwest shelf at that time. These communities were largely structured by substrate type and depth, but there is some evidence that nutrients continued to play a role. Phyllophora spp. was present across much, but not all, of its former range, but at far lower percent cover than previously. The pattern of abundance of Phyllophora in 2006-08 did not correlate with the documented pre-eutrophication pattern from 1966. There is some evidence that faster-growing opportunistic species have hindered to recovery. We conclude that while there was evidence of sustained recovery, by 2008 the macro-epibenthic communities of the northwest shelf of the Black Sea were far from their pre-eutrophication state.